Sociale en economische historici anno 2027: uit de academie, in de wereld! - Baguet, Jelten (TSEG - The Low Countries Journal of Social and Economic History, 2018)
An increasing number of social and economic historians is convinced that they need to step out of their ivory tower and should engage in on-going public debates related to their domains of expertise. Many of the twenty- and thirtysomething researchers are certainly willing to do so, although they currently lack the tools to let their voices be heard in civil society or by policy-makers and businessmen. In this essay, I propose four strategic changes that will strengthen the visibility of Dutch and Flemish social and economic historians as well as their impact on public and private policy-making, namely (1) a diversification of our too narrowly focussed communication strategy, (2) the introduction of ‘duo-jobs’ which allow combining academic work with a career outside academia, (3) an increased cooperation with the business world and (4) the creation of a Centre of Expertise that builds bridges between academic and non-academic partners.